All by myself - Mayer, Mercer, 1943- (New York : Golden Press, 1983)
All the many things a young child can do independently are demonstrated, (tying shoes, riding bike, kicking ball), but there is one thing one cannot do alone.
Keywords: Children's stories, American; Self-reliance -- Fiction